2013
DOI: 10.3109/10826084.2013.824478
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Continuity of Substance Use

Abstract: Guided by rigorous methodology and a life-course perspective, the goal of this research is to address a gap in current knowledge on whether, when, and how strongly intergenerational continuity of substance use exists when examining age-equivalent and developmentally specific stages of the life course. Annual self-reported substance use measures were analyzed from a prospective, longitudinal, and nationally representative sample that originally consisted of 1,725 respondents and their families, who were then in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 53 publications
(62 reference statements)
1
33
1
Order By: Relevance
“…However, we note that almost all other prospective, longitudinal data sources are limited in the same way with respect to a specific geographic locale. Nonetheless, this is the first study to demonstrate IG continuity among a predominantly minority sample (i.e., 90% of the families were non-White in RIGS compared to 22% in the Oregon Youth Study, 16 27% in the National Youth Survey Family Study, 15 and 59% in the Seattle Social Development Study Intergenerational Project 17 ), suggesting the importance of IG continuity in an ethnically diverse sample.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, we note that almost all other prospective, longitudinal data sources are limited in the same way with respect to a specific geographic locale. Nonetheless, this is the first study to demonstrate IG continuity among a predominantly minority sample (i.e., 90% of the families were non-White in RIGS compared to 22% in the Oregon Youth Study, 16 27% in the National Youth Survey Family Study, 15 and 59% in the Seattle Social Development Study Intergenerational Project 17 ), suggesting the importance of IG continuity in an ethnically diverse sample.…”
Section: Discussionmentioning
confidence: 69%
“…Surprisingly little published work is available to quantify the specific direct and indirect effects of a parent's cannabis use during adolescence on offspring's cannabis use, particularly when limited to papers meeting the methodological rigor to study IG hypotheses. 14 One exception is Knight and colleagues 15 who report a direct relationship between frequency of parental use of cannabis during both adolescence and emerging adulthood and frequency of child cannabis use during these same time periods. Kerr, Tiberio, and Capaldi 16 also examined the relationship between frequency of parent cannabis use during adolescence (retrospectively reported for mothers but prospectively reported for fathers) and offspring cannabis use onset during adolescence and found an indirect IG effect via two social context variables – peer marijuana use and peer delinquency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is little research from which to make confident predictions about the influence of changing norms and marijuana legalization on those who are actively parenting. Notably, parental substance use is strongly associated with use among their children [810], so to the extent marijuana legalization increases use among parents then their children would be at increased risk for use. One study [11], based in part on SSDP data, confirmed that parents’ marijuana-specific norms and use were associated with child substance use.…”
Section: Parents’ Approval and Perceived Harm Of Adult And Adolescentmentioning
confidence: 99%
“…A large body of studies shows a link between parent and child substance use [4,5,7,8], including marijuana use [9,10]. Studies of the association between parent and offspring substance use typically have looked at either “current” or “lifetime” substance use by parents without regard to the timing of use in the parent's life course.…”
Section: Parent and Grandparent Marijuana Usementioning
confidence: 99%